Universality of Returning Electron Wave Packet in High-Order Harmonic Generation with Midinfrared Laser Pulses - Le, Anh-Thu; Wei, Hui; Jin, Cheng; Tuoc, Vu Ngoc; Morishita, Toru; Lin, C. D. (My University, 2014)
We show that a returning electron wave packet in high-order harmonic generation (HHG) with midinfrared laser pulses converges to a universal limit for a laser wavelength above about 3 μm. The results are consistent among the different methods: a numerical solution of the time-dependent Schrödinger equation, the strong-field approximation, and the quantum orbits theory. We further analyze how the contribution from different electron “trajectories” survives the macroscopic propagation in the medium. Our result thus provides a new framework for investigating the wavelength scaling law for the HHG yields.